Design and Development of an SDLC-Based E-Learning Application as a Learning Medium Using the Blended Learning Model - Deni Ramadhan; Zulham Sitorus; Melva Sari Penjaitan (Bulletin of Information Technology (BIT), 2024)
Education in the digital era demands the application of innovative learning methods to enhance effectiveness and student engagement. This research aims to design the workflow of an e-learning application that integrates the blended learning model, with a focus on SMA Nurcahaya as a case study. The blended learning model combines face-to-face instruction with online learning, providing flexibility in the teaching and learning process and leveraging technology to enhance the student learning experience. The research methodology includes needs analysis, system design, and e-learning development. Needs analysis was conducted through surveys and interviews with teachers and students to identify specific needs and challenges. Based on these findings, the design and development of the e-learning system incorporated features such as interactive learning materials, discussion forums, online quizzes, and progress tracking. The design process utilized the latest technology to ensure optimal performance and accessibility. The design was evaluated by assessing its effectiveness in meeting the needs of SMA Nurcahaya and its ability to support the teaching and learning process while increasing student engagement. The evaluation results indicated that this e-learning design is effective in boosting learning motivation and facilitating access to learning materials. The research concludes that an e-learning design with a blended learning model can be an effective solution for improving the quality of education in the digital era.